Genetic structure of disjunct Argentinean populations of the subtropical tree Anadenanthera colubrina var. cebil (Fabaceae) - Barrandeguy, María Eugenia (2014)
Anadenanthera colubrina var. cebil is a native South American tree species inhabiting seasonally dry tropical forests (SDTFs). Its current disjunct distribution presumably represents fragments of a historical much larger area of this forest type, which has also been highly impacted by human activities. In this way the hypothesis of this study is that the natural populations of A. colubrina var. cebil from Northern Argentina represent vestiges of ancient fragmentation, but they are additionally influenced by a certain degree of gene flow among them. We aimed to analyze the genetic structure of both nuclear and chloroplast DNA to evaluate the relative role of ancient and recent fragmentation on intraspecific diversity patterns. Sixty-nine individuals of four natural populations were analyzed using eight nuclear microsatellites (ncSSR) and four chloroplast microsatellite loci (cpSSR). The level and distribution of genetic variation were estimated by standard population genetic parameters and Neighbor Joining as well as Bayesian analyses. The eight ncSSR loci were highly polymorphic, while genetic diversity of cpSSRs was low. Nuclear SSRs displayed lower genetic differentiation among populations than cpSSR haplotypes (FST 0.11 and 0.95, respectively). However, high differentiation between phytogeographic provinces was observed in both genomes. The high genetic differentiation detected emphasizes the role of ancient fragmentation. However, the Paranaense province also shows the effects of recent fragmentation on genetic structure, whereas gene flow by pollen preserves the effects of genetic drift in the Yungas province.